Public policies for favelas in Osasco-SP and the production of the peripheral city - Rios, Joana da Costa Manso Ramos Alves (National Journal of City Management, 2022)
The purpose of this article is to analyze municipal actions in the slums of the city of Osasco, in São Paulo State, through public policies launched to face the precariousness of housing in this type of settlement, whether for removal or maintenance. It seeks to evaluate the administrative structure to understand the state organization to carry out the proposed interventions as well as legislative changes in order to make regulations more flexible, the programs created and the effectiveness of these actions. In order to carry out this study, municipal legislation from the mid-1970s to the present day, referring to the administrative structure and urban regulation, was analyzed. We also searched the literature for studies that report the experience of the city of São Paulo, considering that both cities participate in the same urbanization process. Such policies resulted in an urban design that fell short of the norms, but that characterize peripheral cities.